Clinical practice guidelines for the diagnosis and management of acute otitis media in children—2018 update. Issue 4 (August 2020) - Hayashi, Tatsuya; Kitamura, Ken; Hashimoto, Sho; Hotomi, Muneki; Kojima, Hiromi; Kudo, Fumiyo; Maruyama, Yumiko; Sawada, Shoichi; Taiji, Hidenobu; Takahashi, Goro; Takahashi, Haruo; Uno, Yoshifumi; et al.
Abstract: Objective: "Clinical Practice Guidelines for the Diagnosis and Management of Acute Otitis Media in Children—2018 update (2018 Guidelines)" aim to provide appropriate recommendations about the diagnosis and management of children with acute otitis media (AOM), including recurrent acute otitis media (recurrent AOM), in children under 15 years of age. These evidence-based recommendations were created with the consensus of the subcommittee members, taking into consideration unique characteristics of bacteriology and antimicrobial susceptibilities of AOM pathogens in Japan, as well as global advances in vaccines. Methods: The subcommittee re-evaluated key clinical issues based on SCOPE (a master plan of the guidelines) and created clinical questions (CQ) about the diagnosis and management of AOM patients. A literature search of the publications from 2013 to 2016 were added to the Guidelines 2013, not only to assess the evidence on the effectiveness of vaccines, but also to provide up to date information of the bacteriology and antimicrobial susceptibilities of AOM causative pathogens in Japan. Results: We have proposed guidelines for disease severity-based management of AOM patients, after classifying AOM severity into mild, moderate, and severe, based on age, clinical manifestations, and otoscopic findings. Conclusions: Precise otoscopic findings are essential for judging AOM severity, which can lead to appropriate management of AOM patients.